You are on page 1of 5

# DETERMINANTS 55

www.thinkiit.in
2.3 Special Determinants :
(1) Symmetric determinant.
c f g
f b h
g h a
= abc + 2fgh – af
2
– bg
2
– ch
2
In this the elements a
ij
= a
ji
or the elements situated at equal distance from the diagonal are equal
both in magnitude and sign.
(2) Skew symmetric determinant of odd order.
0 a c
a 0 b
c b 0
÷
÷
÷
= 0.
All the diagonal elements are zero and a
ij
= – a
ji
or the elements situated at equal distance from the
diagonal are equal in magnitude but opposite in sign. Its value is zero.
(3) Circulant
b a c
a c b
c b a
= – (a
3
+ b
3
+ c
3
– 3abc)
The three rows or columns are the cyclic arrangement of the letters a, b, c, i.e. a, b, c ; b, c, a
and c, a, b respectively.
(4) Factors of three important determinants :
(i)
2 2 2
c b a
c b a
1 1 1
= (a – b) (b – c) (c – a)
(ii)
3 3 3
c b a
c b a
1 1 1
=(a – b) (b – c) (c – a) (a + b + c)
(iii)
3 3 3
2 2 2
c b a
c b a
1 1 1
= (a – b) (b – c) (c – a) (ab + bc + ca)
DETERMINANTS 57
www.thinkiit.in
Ex.3 Solve the equation
x +α x x
x x +α x
x x x +α
=0, (a ≠0).
Sol. Let A =
o +
o +
o +
x x x
x x x
x x x
= (x + a)
a x x
x a x
+
+
– x
o + x x
x x
+ x
x x
x x o +
= (x + a) [(x + a)
2
– x
2
] – x [x (x + a) – x
2
] + x [x
2
– x (x + a)]
= (x + a)
3
– x
2
(x + a) – ax
2
– ax
2
= (x + a)
3
– x
3
– 3ax
2
= x
3
+ 3ax
2
+ 3a
2
x + a
3
– x
3
– 3ax
2
= 3a
2
x + a
3
Equating it to zero, we have
3a
2
x + a
3
= 0 ¬ x = –
3
a
Ex.4 If a, b and c are real numbers, and
∆ =
b+c c +a a+b
c +a a+b b+c
a+b b+c c +a
=0
Show that either a +b +c =0 or a =b =c
Sol. Here, A =
a c c b ) c b a ( 2
c b b a ) c b a ( 2
b a a c ) c b a ( 2
+ + + +
+ + + +
+ + + +
(C
1
÷ C
1
+ C
2
+ C
3
)
= 2 (a + b + c)
a c c b 1
c b b a 1
b a a c 1
+ +
+ +
+ +
= 2 (a + b + c)
b c a b 0
a c c b 0
b a a c 1
÷ ÷
÷ ÷
+ +
(R
2
÷ R
2
– R
1
; R
3
÷ R
3
– R
1
)
= 2 (a + b + c) × 1
b c a b
a c c b
÷ ÷
÷ ÷
= 2 (a + b + c) [(b – c) (c – b) – (b – a) (c – a)]
= 2 (a + b + c) [bc – c
2
– b
2
+ bc – bc + ac + ab – a
2
]
= 2 (a + b + c) (ab + bc + ca – a
2
– b
2
– c
2
)
Equating A to zero, we have
2 (a + b + c) (ab + bc + ca – a
2
– b
2
– c
2
) = 0
¬ Either a + b + c = 0 or ab + bc + ca = a
2
+ b
2
+ c
2
¬ Either a + b + c = 0 or a = b = c
DETERMINANTS 59
www.thinkiit.in
Ex.8 If a, b, c are in AP, prove that :
x +2 x +3 x +2a
x +3 x +4 x +2b
x +4 x +5 x +2c
=0
Sol. Let A =
c 2 x 5 x 4 x
b 2 x 4 x 3 x
a 2 x 3 x 2 x
+ + +
+ + +
+ + +
=
) a c ( 2 2 2
) a b ( 2 1 1
a 2 x 3 x 2 x
÷
÷
+ + +
(R
2
÷ R
2
– R
1
; R
3
÷ R
3
– R
1
)
=
) a b ( 4 ) a c ( 2 0 0
) a b ( 2 1 1
a 2 x 3 x 2 x
÷ ÷ ÷
÷
+ + +
(R
3
÷ R
3
– 2r
2
)
= [2 (c – a) – 4 (b – a)]
1 1
3 x 2 x + +
= [2c – 2a – 4b + 4a] (x + 2 – x – 3)
= [2c + 2a – 4b] (–1) = (4b – 2a – 2c) (....1)
Since, a, b, c are in AP,
2b = a + c
4b = 2a + 2c
Hence by (1), A = 0
Ex.9 Prove that
2 2 2
2 2 2
2 2 2
(b+c) a a
b (c +a) b
c c (a+b)
=2abc (a +b +c)
3
Sol. Replacing C
2
by C
2
– C
1
and C
3
by C
3
– C
1
, we have
A =
2 2 2
2 2 2
2 2 2 2 2
c ) b a ( 0 c
0 b ) a c ( b
) c b ( a ) c b ( a ) c b (
÷ +
÷ +
+ ÷ + ÷ +
= (a + b + c)
2
c b a 0 c
0 b a c b
c b a c b a bc 2 c b
2
2
2 2
÷ +
÷ +
÷ ÷ ÷ ÷ + +
Replacing R
1
by R
1
– R
2
– R
3
, we have
A = (a + b + c)
2
c b a 0 c
0 b a c b
b 2 c 2 bc 2
2
2
÷ +
÷ +
÷ ÷
Replacing C
2
by C
3
+
b
1
C
1
and C
3
by C
3
+
c
1
C
1
, we have
A = (a + b + c)
2
b a
b
c
c
c
b
a c b
0 0 bc 2
2
2
2
2
+
+
= 2bc (a + b + c)
2
[(a + c) (a + b) – bc]
= 2bc (a + b + c)
2
(a
2
+ ab + bc – bc)
= 2abc (a + b + c)
3
DETERMINANTS 61
www.thinkiit.in
Q.1 If A =
(
¸
(

¸

1 2
5 2
and B =
(
¸
(

¸
÷
5 2
3 4
, verify that |AB| = |A| |B|
Q.2 Without expanding evaluate the determinant
b a ab b a
a c ca a c
c b bc c b
2 2
2 2
2 2
+
+
+
Q.3 Without expanding evaluate the determinant
ab c c 1
ac b b 1
bc a a 1
2
2
2
÷
÷
÷
Q.4 Without expanding evaluate the determinant
1 ) a a ( ) a a (
1 ) a a ( ) a a (
1 ) a a ( ) a a (
2 z z 2 z 2
2 y y 2 y y
2 x x 2 x x
÷ ÷
÷ ÷
÷ ÷
÷ +
÷ +
÷ ÷
Q.5 Without expanding evaluate the determinant
) sin( cos sin
) sin( cos sin
) sin( cos sin
o + ¸ ¸ ¸
o + | | |
o + o o o
Q.6 Prove that
c 1 1 1
1 b 1 1
1 1 a 1
+
+
+
= abc 1 |
¹
|

\

+ + +
c
1
b
1
a
1
1 = abc + ab + bc + ca
Q.7 Prove that
b 2 a c a c
b a 2 c b c
b a c 2 b a
+ +
+ +
+ +
= 2(a + b + c)
3
Q.8 Prove that
ab c ) b a (
ca b ) a c (
bc a ) c b (
2 2
2 2
2 2
+
+
+
= (a
2
+ b
2
+ c
2
) (a + b + c) (b – c) (c – a) (a – b)
Q.9 Show that
2 2
2 2
2 2
b a 1 a 2 b 2
a 2 b a 1 ab 2
ab 2 ab 2 b a 1
÷ ÷ ÷
+ ÷
÷ ÷ +
= (1 + a
2
+ b
2
)
2
Q.10 Solve :
8 x 3 3 3
3 8 x 3 3
3 3 8 x 3
÷
÷
÷
= 0
Q.11 If x = y = z and
3 2
3 2
3 2
z 1 z z
y 1 y y
x 1 x x
+
+
+
= 0, then prove that 1 + xyz = 0
Q.12 If a, b, c are all positive and are pth, qth and rth terms respectively of a G.P. then prove that
1 r c log
1 q b log
1 p a log
= 0
Q.13 Find the area of a triangle with vertices : (–3, 5), (3, –6), (7, 2)
Q.14 Find the value of ì so that the points given below are collinear (ì, 2 – 2ì), (–ì + 1, 2ì) and (–4, –ì, 6 – 2ì)
Q.15 Using determinants, find the area of the triangle, whose vertices are (–2, 4), (2, –6) and (5, 4). Are the given
points collinear ?
UNSOLVED PROBLEMS
EXERCISE – I
DETERMINANTS 63
www.thinkiit.in
Q.11 Using the properties of determinants, prove that [C.B.S.E. 2006]
(a)
y x x z z y
q p p r r q
b a a c c b
+ + +
+ + +
+ + +
= 2
z y x
r q p
c b a
(b)
c 3 c b c a
b c b 3 b a
c a b a a 3
÷ ÷
÷ ÷
+ ÷ + ÷
= 3(a + b + c) (ab + bc + ca)
Q.12 Using the properties of determinants, prove that [C.B.S.E. 2007]
(a)
) b a ( ab ab 1
) a c ( ca ca 1
) c b ( bc bc 1
+
+
+
= 0. (b)
xy z z
zx y y
yz x x
2
2
2
= (x – y) (y – z) (z – x) (xy + yz + zx)
Q.13 If x, y, z are different and
3 2
3 2
3 2
z 1 z z
y 1 y y
x 1 x x
+
+
+
= 0, show that xyz = –1. [C.B.S.E. 2008]
Q.14 If a, b and c are all positive and distinct, show that A =
b a c
a c b
c b a
has a negative value.
[C.B.S.E. 2008]
Q.15 Solve for x :
8 x 3 3 3
3 8 x 3 3
3 3 8 x 3
÷
÷
÷
= 0. [C.B.S.E. 2008]
Q.16 Using the properties of determinants. [C.B.S.E. 2008]
(a)
3 2
3 2
3 2
az 1 z z
ay 1 y y
ax 1 x x
+
+
+
= (1 + axyz) (x – y) (y – z) (z – x)
(b)
2 2
2 2
2 2
b a 1 a 2 b 2
a 2 b a 1 ab 2
b 2 ab 2 b a 1
÷ ÷ ÷
+ ÷
÷ ÷ +
= (1 + a
2
+ b
2
)
3
(c)
1 x x
x 1 x
x x 1
2
2
2
= (1 – x
3
)
2
(d)
3 2
3 2
3 2
c ab c 1
b ca b 1
a bc a 1
+
+
+
= – (a – b) (b – c) (c – a) (a
2
+ b
2
+ c
2
).
Q.17 Using properties of determinants, prove the following :
[C.B.S.E. 2009]
(a)
2 2
2 2
2 2
b a 1 a 2 b 2
a 2 b a 1 ab 2
b 2 ab 2 b a 1
÷ ÷ ÷
+ ÷
÷ ÷ +
= (1 + a
2
+ b
2
)
3
(b)
1 c cb ca
bc 1 b ba
ac ab 1 a
2
2
2
+
+
+
= 1 + a
2
+ b
2
+ c
2
(c)
q 3 p 6 1 p 3 6 3
q 2 p 3 1 p 2 3 2
q p 1 p 1 1
+ + +
+ + +
+ + +
= 1 (d)
b a a c c b
a c c b b a
c b a
+ + +
÷ ÷ ÷
= a
3
+ b
3
+ c
3
– 3abc